2018
DOI: 10.5797/jnet.cr.2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Retrieval of a Migrated Coil with a Stent Retriever

Abstract: Objective: Coil migration is a complication related to endovascular coil embolization. In this study, we report a patient in whom an intraoperatively migrated coil was successfully retrieved using a stent retriever.Case Presentation: A 57-year-old male. To treat an unruptured aneurysm of the right internal carotid artery, endovascular coil embolization was performed. During embolization, one end of a framing coil migrated into the parent artery, and it was retrieved using a microsnare. However, this resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…14 Four cases were symptomatic but had no permanent complications. [15][16][17] Interestingly 5 years following CE, one of the patients developed a 30-minutes right heminumbness which was correspondent to a migrated stretched coil that extended down to the descending aorta. 18 Balloon-assisted coil reimplantation technique was utilized in three patients, coil retrieval in 15 patients, coil crushing against the vessel wall in five patients while burring the trailing end of the coil was adopted in six patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Four cases were symptomatic but had no permanent complications. [15][16][17] Interestingly 5 years following CE, one of the patients developed a 30-minutes right heminumbness which was correspondent to a migrated stretched coil that extended down to the descending aorta. 18 Balloon-assisted coil reimplantation technique was utilized in three patients, coil retrieval in 15 patients, coil crushing against the vessel wall in five patients while burring the trailing end of the coil was adopted in six patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Observing that the displaced coil proximally shifted hand in hand while retracting the expanded stent, they continued coil retrieval concomitant with partial stent resheathing till the coil is entirely withdrawn. Similarly, Fujii et al 17 reported the use of Trevo XP ProVue in the successful retrieval of a displaced coil mass out of an incidentally discovered cavernous ICA aneurysm into the MCA bifurcation after failed retrieval via the snaring device.…”
Section: Coil Retrievalmentioning
confidence: 96%